RESIDENTIAL PROBLEMS AND PROCESSES OF PRIVATIZATION IN THE YEARS OF INDEPENDENCE (Scientific journal of the Fergana State University, 2023)
This article focuses on scientific research conducted in the field of housing stock management in Uzbekistan, focuses on the formation of organizational foundations for managing this area, determining the directions of activity of industry enterprises and expanding types. the services they provide. In recent years, scientific research has been focused on improving the quality and efficiency of this activity, in particular on the decentralization of the housing stock management system and reducing the participation of the state in management.